2017
DOI: 10.1590/0104-6632.20170342s20150500
|View full text |Cite
|
Sign up to set email alerts
|

Oil Removal from Produced Water by Ultrafiltration using Polysulfone Membrane

Abstract: -The present paper deals with the ultrafiltration (UF) of produced water using a polysulfone membrane. Membranes were prepared by the phase inversion technique using polysulfone (PSf) polymer base, poly vinyl pyrrolidone (PVP) additive and N-methyl-2-pyrrolidone (NMP) solvent. Prepared UF membranes were characterized by determining the surface morphology by scannaing electron microscopy (SEM), atomic force microscopy (AFM), porosity, (iii) water contact angle, equilibrium water content and pure water flux, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 22 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…The experimental data exhibited that the prepared membrane provided chemical oxygen demand, total organic carbon, and oil and grease content reductions in the order of 83.1%, 96.3%, and 99.7% with final flux and fouling of about 84.1 L m −2 h −1 and 63.0%, respectively . Applications of neat PSf and PES membranes for PW treatment are reported in few other studies …”
Section: Introductionmentioning
confidence: 79%
“…The experimental data exhibited that the prepared membrane provided chemical oxygen demand, total organic carbon, and oil and grease content reductions in the order of 83.1%, 96.3%, and 99.7% with final flux and fouling of about 84.1 L m −2 h −1 and 63.0%, respectively . Applications of neat PSf and PES membranes for PW treatment are reported in few other studies …”
Section: Introductionmentioning
confidence: 79%
“…Moreover, Figure 6 shows the average droplet size by using a Zetasizer analyser, which was in the range from 3.2-7.3 µm depending on the concentration of oil in the emulsion. As the concentration of oil in the emulsion increased, smaller oil droplets will have aggregated to form larger droplets, with these larger droplets increasingly likely to cause pore blocking [34].…”
Section: Effect Of Oil Concentration On Permeate Fluxmentioning
confidence: 99%
“…Several researchers have examined the use of UF membranes for handling produced water [10][11][12][13][14]. The previous study showed that UF treatment was able to reject 87.82 % of COD, 98.7 % of oil, 90.5 % of Total Organic Compound (TOC) from produced water by using 20 kDa UF membrane [12].…”
Section: Introductionmentioning
confidence: 99%